Radiomics-guided checkpoint inhibitor immunotherapy for precision medicine in cancer: A review for clinicians - Zhou, Huijie; Luo, Qian; Wu, Wanchun; Li, Na; Yang, Chunli; Zou, Liqun (Frontiers in Immunology, 2023)
Immunotherapy using Immune checkpoint inhibitors (ICIs) is a breakthrough in oncology development and has been applied to multiple solid tumors. However, unlike traditional cancer treatment approaches, Immune checkpoint inhibitors (ICIs) initiate indirect cytotoxicity by generating inflammations, which cause enlargement of the lesion in some cases. Therefore, rather than declaring progressive disease (PD) immediately, confirming upon follow-up radiological evaluation after four–eight weeks is suggested according to immune-related Response Evaluation Criteria in Solid Tumors (ir-RECIST). Given the difficulty for clinicians to immediately distinguish pseudoprogression from true disease progression, we need novel tools to assist in this field. Radiomics, an innovative data analysis technique that quantifies tumor characteristics through high-throughput extraction of quantitative features from images can enable the detection of additional information from early imaging. This review will summarize the recent advances in radiomics concerning immunotherapy. Notably, we will discuss the potential of applying radiomics to differentiate pseudoprogression from PD to avoid condition exacerbation during confirmatory periods. We also review the applications of radiomics in hyperprogression, immune-related biomarkers, efficacy, and immune-related adverse events (irAEs). We found that radiomics have shown promising results in precision cancer immunotherapy with early detection in non-invasive ways.